Strategies to sensitize cancer cells to immunotherapy. Issue 8 (3rd August 2021) - George, Andrew; Sahin, Ilyas; Carneiro, Benedito A.; Dizon, Don S.; Safran, Howard P.; El-Deiry, Wafik S.
ABSTRACT: Recent years have seen the emergence of immunotherapy as a promising modality for treating a variety of cancers. However, the initial data have led to the ultimate reality that such a treatment does not work effectively in all cancers, nor does it universally result in long-lasting benefits, which can be partly attributed to the development of drug resistance- itself a major challenge. Worse, in some cases, immunotherapy can lead to accelerated tumor growth known as hyperprogression. Tumor sensitization is being pursued as a means to circumvent resistance to immunotherapy, and perhaps as a means to prevent hyperprogression. Such approaches aim to counteract features of immune resistance demonstrated by refractory tumors, paving the way for improved treatment effectiveness when standard immunotherapies such as immune checkpoint inhibitors are utilized. Sensitizing agents can be categorized by whether their target is a tumor-intrinsic or a tumor cell-extrinsic factor. Tumor-intrinsic sensitization strategies act directly on cancer cells, suppressing their anti-immune tendencies, whereas tumor cell-extrinsic sensitization strategies target the tumor microenvironment to more effectively mediate the desired therapeutic effects of immunotherapy.